Evidentiality in climate change discourse by King Charles III - Kapranov, Oleksandr (Vestnik za tuje jezike, 2024)
The issue of climate change is a serious challenge to human beings, the environment, the planet in general and individual countries in particular (Gardiner, 2024; Yasmin, 2024). As far as the issue of climate change in individual countries is concerned, in the United Kingdom (UK), for instance, climate change resurfaces quite routinely as a topic of political debates by the major political actors (Kapranov, 2024a; Ruiu et al., 2024), who usually regard it through the lens of scientific evidence (Sébastien et al., 2014; Strassheim & Kettunen, 2014). The current British monarch, King Charles III, is also reported to use science-based evidence in his public speeches and written communication on the issue of climate change (Lovelock & Lovelock, 2013). Presently, however, little is known about how evidence, and more specifically, evidentiality are represented in King Charles III’s speeches on this issue. In light of the lack of studies on evidentiality in King Charles III’s speeches on climate change, the article presents a mixed-methods study, which aims to (i) identify, (ii) classify and (iii) analyse the categories of evidentiality in a corpus of speeches on cli-mate change delivered by King Charles III. The study is informed by the view of evidentiality as a category in its own right (Aikhenvald, 2004), which expresses “the kinds of evidence a person has for making factual claims” (Anderson, 1986: 273). Guided by Aikhenvald’s (2004) classification of evidentiality, the analysis of the corpus revealed that evidentiality in King Charles III’s speech-es on climate change was manifested by several categories, namely (i) assumption, (ii) hearsay, (iii) inference, (iv) non-visual sensory, (v) quotative, and (vi) visual. Furthermore, the analysis established that the quotative category of evidentiality was dominant in the corpus. The finding was taken to indicate that King Charles III’s speeches on the issue of climate change involved, to a substantial degree, evidence-based judgements on the matter.
Keywords: climate change; evidencialnost; evidentiality; king Charles III; kralj Karl III; podnebne spremembe